Evaluation of a collaborative and distributed aircraft design environment, enabled by microservices and cloud computing - Chen, Xin; Isoldi, Adriano; Riaz, Atif; Mourouzidis, Christos; Keskin, Akin; Smith, Dale; Guenov, Marin D.; Pachidis, Vassilios (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Presented in this paper are the outcomes from the evaluation of a distributed aircraft design environment, based on microservices and cloud computing. The evaluation was performed on a representative airframe-engine optimization case study, including the engine, wing aero-structural geometry, and high-lift devices. The (computational) design process involved multiple distributed design teams and design tools. The latter were implemented with different programming languages and deployed on the Azure cloud service. As a benchmark, the same case study was performed using the traditional email/document-based approach to design collaboration. Compared with the traditional collaboration, the cloud-based approach substantially reduced the time for design iterations between the design teams. This was mainly due to the fast remote access of models/tools on the cloud and automation of data exchange. Also, the exercise indicated that the cloud-based approach is more flexible with regard to orchestrating the computational workflows and optimization studies, while protecting the Intellectual Property (IP) of the collaborating partners.